Little mates busy book - Ayob, Nurzuraimie; Azman, Nur’Aliyah; Mohd Zan, Nur Diyanah; Abdul Aziz, Nadiatul Izzah; Selamat, Nordibradini (Universiti Teknologi Mara, Kedah, 2022)
Early learning is the foundation of a good education. Children can recognize letters and numbers as early as two years old. It can be stimulated by children with a much-needed head start with activity books; children will have the life skills they need to be aware of what is happening in their surroundings. This busy book provides children with fun-loving activities that help build that level of awareness and strengthen knowledge about the environment and people. Activities like matching, tracing, puzzling and finding patterns and colours help build fine motor skills. In contrast, sight word activities build every child’s much-needed knowledge base, ensuring skills to retain knowledge are sharpened. The objectives of this book are to practice the newly acquired skill, develop the reading ability and encourage the children's critical thinking